Acelerar la transformación digital en tiempos difíciles - Valdez, Carlos (2021)
Carlos Valdez (Perú) - Presentador; Diego Carrillo (Perú) - Expositor; Juan Pacheco (Perú) - Expositor; Marushka Chocobar (Perú) - Expositora; Hideyuki Iwata (Japón) - Expositor; Hugo Chang (Perú) - Expositor; Raúl Hugo - (Perú) - Expositor; Mesías Guevara (Perú); Sergio Salas (Perú) - Moderador